New simulation approach for tuneable trapezoidal and rectangular piezoelectric bimorph energy harvesters - Salim M.; Salleh H.; Loh E.W.K.; Khir M.; Salim D. (Springer Verlag, 2023)
Energy harvesting; Nanocantilevers; Natural frequencies; Open circuit voltage; Piezoelectricity; Resonance; Bimorph cantilever; Energy Harvester; Finite element software; Frequency ranges; Operating frequency; Piezoelectric bimorphs; Resonance frequencies; Simulation approach; Finite element method